Development of physical 3D model of maternal-fetal to study light interaction through tissue - Nur Anida, Jumadi; Kok, Beng Gan; Mohd. Alauddin, Mohd. Ali, Prof. Dr.; Zahedi, Edmond, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/